Impact of FDI on Import Demand and Export Supply Functions of Pakistan: An Econometric Approach - Tabassum, Uzma; Nazeer, Munazah; Siddiqui, Afaq Ahmed (Journal of Basic & Applied Sciences, 2012)
FDI tends to increase the host country’s imports, because Multi-National Corporations (MNCs) often have a high tendency to import intermediate inputs, capital goods and services that are not readily available in the recipient countries as well as it also affect exports from the export supply side. We investigated the relationship between foreign direct investment (FDI) and imports demand as well as between foreign direct investment (FDI) and exports supply of Pakistan for the time span of 37 years range from 1973 to 2009. Our analysis emphasized on the existence of long run equilibrium relationship between FDI and imports demand & exports supply of Pakistan using econometric techniques (Co-integration Analysis and Error correction mechanism). The co-integration analysis of import demand showed stable long run equilibrium relation-ship between real import and FDI results of export expressed that FDI has positive relation with real exports in the long run, but the coefficient is statistically insignificant. It suggested that the inflow of FDI has largely been directed toward import-substitution industries or production for the domestic market while little has gone toward export-oriented industries. That is long run policies will be fruitful to be implemented. While the short term dynamics as analyzed by the error correction mechanism (ECM) revealed that the short term discrepancies were significant enough to not to converge toward equilibrium and will require a longer time to adjust back in both model. Unilateral causality was detected between real imports (RIM) and FDI which was established both by theoretic